How woody plants adjust above‐ and below‐ground traits in response to sustained drought - Rowland, Lucy; Ramírez‐Valiente, Jose‐Alberto; Hartley, Iain P.; Mencuccini, Maurizio (The New phytologist, 2023)
Summary Future increases in drought severity and frequency are predicted to have substantial impacts on plant function and survival. However, there is considerable uncertainty concerning what drought adjustment is and whether plants can adjust to sustained drought. This review focuses on woody plants and synthesises the evidence for drought adjustment in a selection of key above‐ground and below‐ground plant traits. We assess whether evaluating the drought adjustment of single traits, or selections of traits that operate on the same plant functional axis (e.g. photosynthetic traits) is sufficient, or whether a multi‐trait approach, integrating across multiple axes, is required. We conclude that studies on drought adjustments in woody plants might overestimate the capacity for adjustment to drier environments if spatial studies along gradients are used, without complementary experimental approaches. We provide evidence that drought adjustment is common in above‐ground and below‐ground traits; however, whether this is adaptive and sufficient to respond to future droughts remains uncertain for most species. To address this uncertainty, we must move towards studying trait integration within and across multiple axes of plant function (e.g. above‐ground and below‐ground) to gain a holistic view of drought adjustments at the whole‐plant scale and how these influence plant survival.